Doctoral Training Programmes as Transdisciplinary Research Models for Knowledge Co-Production - Mumuni , Eliasu (Journal of Interdisciplinary Studies in Education, 2022)
Doctoral training programs and centers (DTP/C) serve as the nexus of research and teaching through networking, training, business, and industrial engagements. This paper used systematic reviews on selected searched phrases from Google Scholar, University of Nottingham Library, Research Gate and SCOPUS, and many other credible and indexed journal sites for relevant literature. The study revealed musingly that DTP/C is an advanced transdisciplinary platform of coproducing knowledge to address complex problems. This paper recommends that using a transparent communication process, setting up clear goals and targets with students with noncoercive consent, and strengthening the formal and institutional structures that take care of and address every actor’s need and requirement are critical.